2002
DOI: 10.1016/s1631-0691(02)01423-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of French Guiana Hylinae: implications for the systematic and biodiversity of the Neotropical frogs

Abstract: In this study we used nucleotide sequences from a segment of mitochondrial 16S ribosomal DNA gene to investigate the evolutionary relationships of some French Guiana Hylinae. New sequences, representing the members of different French Guiana frogs-five specimens of the Scinax genus, two Hyla, one Osteocephalus, one Hyalinobatrachium and two Rana as out-group-were examined. In addition, 26 sequences available from GenBank database representing the other subfamilies of the Hylidae were added to our study. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…Scinax cruentommus has been widely reported from Peru, Brazil, Ecuador and Colombia [65], and from French Guiana [7, 42, 80–82]. In our barcoding analyses, a Scinax specimen from PMIR identified as S .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Scinax cruentommus has been widely reported from Peru, Brazil, Ecuador and Colombia [65], and from French Guiana [7, 42, 80–82]. In our barcoding analyses, a Scinax specimen from PMIR identified as S .…”
Section: Discussionmentioning
confidence: 84%
“…cruentommus BRA) differs from S . cruentommus GUF ( sensu [7, 42, 8081]) with genetic distances of 31 to 32%. Unlike S .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses are an expansion of those presented by Funk et al (2012) to include additional sequences of Hypsiboas calcaratus , Hypsiboas dentei , Hypsiboas fasciatus and Hypsiboas raniceps published by Darst and Cannatella (2004), Faivovich et al (2004, 2005), Salducci et al (2002, 2005), Jansen et al (2011), Wiens et al (2005, 2006) and 19 sequences of the nuclear gene RAG-1 (recombination activating gene 1). GenBank accession numbers for the sequences not included in Funk et al (2012) are shown in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Each alignment was compared with available secondary structures (12S and 16S) (Van de Peer et al, 1998) as described in Salducci et al (2002), or with the reading frame (tyrosinase). The analyses were performed on 368 (Scinax)-387 (Rhinella) aligned bp of the 12S rDNA gene, 413-411 bp of the 16S rDNA gene, 388-539 bp of the tyrosinase gene and 1299-1325 bp of the 18S rDNA gene.…”
Section: Molecular Analysismentioning
confidence: 99%
“…1). Sequences of 14 of the hylid samples have already been published in Salducci et al (2002Salducci et al ( , 2005 IdentiWcations of specimens were mainly based on the only available comprehensive reference on anurans of French Guiana (Lescure and Marty, 2000). However, the taxonomy used by these authors may in some aspects be conXicting with the classiWcation used in other parts of the Neotropics.…”
Section: Introductionmentioning
confidence: 99%